1982
DOI: 10.1002/j.1460-2075.1982.tb01363.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptors recognize DNA sequences in and around murine mammary tumour virus DNA.

Abstract: In several rodent cell lines, glucocorticoids increase the transcription of murine mammary tumour virus (MMTV) proviral DNA in a process mediated by the glucocorticoid receptor. To investigate whether a direct interaction between the receptor and specific sequences on the induced genes can be implicated in the hormonal regulation of transcription, filter binding studies were performed with partially purified glucocorticoid receptor of rat liver and eight cloned MMTV proviral probes. Both the 40 000 and the 90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(72 citation statements)
references
References 27 publications
6
66
0
Order By: Relevance
“…The receptor also bound to MTV regions outside the LTR and to mouse genomic sequences flanking endogenous proviral copies (Geisse et al, 1982). The fact that a 45000 Mr receptor fragment, presumably devoid of the 'specifier' domain (see the Introduction), displayed DNA binding in these experiments casts doubt on the physiological significance of such receptor-DNA interactions.…”
Section: Glucocorticoids Modulate Mrna Concentrationmentioning
confidence: 96%
“…The receptor also bound to MTV regions outside the LTR and to mouse genomic sequences flanking endogenous proviral copies (Geisse et al, 1982). The fact that a 45000 Mr receptor fragment, presumably devoid of the 'specifier' domain (see the Introduction), displayed DNA binding in these experiments casts doubt on the physiological significance of such receptor-DNA interactions.…”
Section: Glucocorticoids Modulate Mrna Concentrationmentioning
confidence: 96%
“…To analyze what fragments in the uteroglobin gene region are bound by glucocorticoid receptor we first used nitrocellulose filter binding experiments (Geisse et al, 1982). In these experiments it is useful to compare DNA fragments of similar sizes as larger DNA fragments tend to bind the receptor nonspecifically.…”
Section: Filter Binding and Immunoprecipitation Experimentsmentioning
confidence: 99%
“…In these experiments it is useful to compare DNA fragments of similar sizes as larger DNA fragments tend to bind the receptor nonspecifically. Equally important are assays conducted in the presence of competitor DNA or at salt concentrations higher than 60 mM as in these cases the non-specific binding of the receptor to DNA is markedly reduced (Geisse et al, 1982). With these precautions in mind, it is obvious from the results in Figure Id there is no preferential binding of the receptor to X DNA, we concluded that the sequences around the 5' end of the uteroglobin gene were responsible for the results shown in Figure Figure 1f).…”
Section: Filter Binding and Immunoprecipitation Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The active transcription factor GR is a dimer which is formed on its DNA element, the glucocorticoid response element GRE, in head-to-tail ± tail-to-head fashion. In addition to activating transcription of speci®c target genes which carry the palindromic GRE (Geisse et al, 1982;Hynes et al, 1983), the GR exerts negative in¯uences on the expression of certain genes. In principle, all nuclear receptors seem to possess this ability Beato et al, 1995).…”
mentioning
confidence: 99%